Contradictions and Limitations of Final Offer Selection: The Manitoba Experience - Black, Errol; Silver, Jim (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1990)
This paper analyses Manitoba's experiment with final offer selection for the purpose of clarifying the roots of the conflict it has generated.